Comprehensive Review and Comparative Analysis of Hardware Architectures for Sobel Edge Detector. (6th April 2014) - Singh, Sanjay; Saurav, Sumeet; Saini, Ravi; Saini, Anil Kumar; Shekhar, Chandra; Vohra, Anil
Abstract : This paper presents a comprehensive review and a comparative study of various hardware/FPGA implementations of Sobel edge detector and explored different architectures for Sobel gradient computation unit in order to show the various trade-offs involved in choosing one over another. The different architectures using pipelining and/or parallelism (key methodologies for improving the performance/frame rates) are explored for gradient computation unit in Sobel edge detector. How the different architectures affected performance (in terms of video frame rate and image size) and area (in terms of FPGA resources usages) has been demonstrated. By exploiting the trade-offs between video frame rate, image size, and FPGA resources a designer should be able to find an optimal architecture for a given application.